Peran Teori Psikoanalisis Dalam Pemahaman Karakter Sastra - Monica Tambunan; Syalwa Atikah Harahap; Gresya Anugrah Tampubilin; Sri Hartati Lombu; Yeni Putri Panjaitan; Handiantha Muantha Munthe; Rosmawati Harahap (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Psychoanalytic theory has become an essential tool in understanding literary characters, providing deep insights into motivations, internal conflicts, and psychological development of figures. This study aims to explore the role of psychoanalytic theory in character analysis within Indonesian literature. Using a qualitative approach and literature review, this article examines various literary works that depict the psychological complexities of characters, as well as how psychoanalytic theory can aid readers in understanding the emotional dynamics and behaviors of these figures. The findings indicate that the application of psychoanalytic theory not only enriches character interpretation but also opens discussions about the social and cultural contexts influencing character creation in literature.